Identification of S-Nitrosylated (SNO) Proteins in Entamoeba histolytica Adapted to Nitrosative Stress: Insights into the Role of SNO Actin and In vitro Virulence - Trebicz-Geffen, Meirav; Shahi, Preeti; Nagaraja, Shruti; Vanunu, Shai; Manor, Shiran; Avrahami, Amit; Ankri, Serge (Frontiers in Cellular and Infection Microbiology, 2017)
We have recently reported that Entamoeba histolytica trophozoites can adapt to toxic levels of the nitric oxide (NO) donor, S-nitrosoglutathione (GSNO). Even if the consequences of this adaptation on the modulation of gene expression in NO-adapted trophozoites (NAT) have been previously explored, insight on S-nitrosylated (SNO) proteins in NAT is missing. Our study aims to fill this knowledge gap by performing a screening of SNO proteins in NAT. Employing SNO resin-assisted capture (RAC), we identified 242 putative SNO proteins with key functions in calcium binding, enzyme modulation, redox homeostasis, and actin cytoskeleton. Of the SNO proteins in NAT, proteins that are associated with actin family cytoskeleton protein are significantly enriched. Here we report that the formation of actin filaments (F-actin) is impaired in NAT. Consequently, the ability of NAT to ingest erythrocytes and their motility and their cytopathic activity are impaired. These phenotypes can be imitated by treating control parasite with cytochalasin D (CytD), a drug that binds to F-actin polymer and prevent polymerization of actin monomers. Removal of GSNO from the culture medium of NAT restored the sensitivity of the parasite to nitrosative stress (NS) and its ability to form F-actin formation and its virulence. These results establish the central role of NO in shaping the virulence of the parasite through its effect on F-actin formation and highlight the impressive ability of this parasite to adapt to NS.